Peat-derived Streptomyces spp. isolated from edamame rhizosphere with plant growth-promoting properties - IRA ERDIANDINI; ARIS TJAHJOLEKSONO; RIKA INDRI ASTUTI; EDI HUSEN; ARIS TRI WAHYUDI (Society for Indonesian Biodiversity, 2025)
Abstract. Erdiandini I, Tjahjoleksono A, Astuti RI, Husen E, Wahyudi AT. 2025. Peat-derived Streptomyces spp. isolated from edamame rhizosphere with plant growth-promoting properties. Biodiversitas 26: 326-334. Peatlands, which are known for their high organic matter content, are common habitats for actinomycetes. These microorganisms have been recognized for their potential as plant growth promoters. However, there have been limited reports on peat-derived actinomycetes with plant growth-promoting properties, especially in edamame-cultivated peatlands. This study aimed to isolate and investigate plant growth-promoting actinomycetes in the rhizosphere of edamame-cultivated peatlands. The results showed that a total of 46 strains were isolated from the edamame rhizosphere during the anthesis and reproductive phase. Importantly, 36 of these strains were found to be biologically safe, as showed by the negative hemolysis and hypersensitivity test. All 36 strains produced indole-3-acetic acid in the range of 2.42 to 50.07 µg/mL. Based on the in vivo plant growth-promoting activity assay, strains RT34, AR26, AR39, and BT59 promoted the highest primary root growth of edamame sprouts. Interestingly, the acetylene reduction assay revealed that only RT34 and AR39 strains exhibited nitrogenase activity as high as that of Azotobacter sp. as a positive control. The nitrogenase activity of these strains was up to 27.42 nmol C2H4 h-1tube-1 and 28.10 nmol C2H4 h-1tube-1. Furthermore, quantitative phosphate solubilization assay showed phosphate solubilization up to 527.76 µg/mL in the range of 258.31 to 527.76 µg/mL. Based on 16S rRNA sequencing, these strains were closely related to the genus Streptomyces. The finding of present results strongly indicates that these Streptomyces strains have plant growth-promoting properties and can be proposed as biostimulants to enhance edamame growth in peatlands.